Advantage Of Physical Methods Of Treatment Of Patients With Neurocirculatory Dystonia - Sultanova Feruza Khoshimovna (Genius Journals, 2024)
The article presents questions devoted to modern aspects of the use of therapeutic physical factors in patients with neurocirculatory dystonia.
Keywords: neurocirculatory autonomic dysfunction; method; dystonia; physiotherapy